Jonathan H. Turner, Alexandra Maryanski, Anders Klostergaard Petersen, and Armin W. Geertz, The Emergence and Evolution of Religion: By Means of Natural Selection - Kundtová Klocová, Eva (Journal for the study of religion, nature and culture, 2020)
Jonathan H. Turner, Alexandra Maryanski, Anders Klostergaard Petersen, and Armin W. Geertz, The Emergence and Evolution of Religion: By Means of Natural Selection